La femme créatrice est l'homme le plus seul au monde : roman familial et problèmes de la création au féminin dans La montagne secrète de Gabrielle Roy - Lamarre, Sylvie (Université du Québec à Montréal, 1995)
Keywords: 1900-1999; 1960-1969; IREF; amériques; canada; discipline; mémoires/thèses; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques